Late Antenatal Booking and its Predictors in Lundu District of Sarawak, Malaysia - Helmy, Hazmi; Sam, Froze Jiee; Razitasham, Safii (Department of Community Health, Universiti Kebangsaan Malaysia Medical Center., 2018)
Antenatal care is widely acknowledged as an effective tool to prevent adverse outcomes in pregnant women and their children. In Malaysia, early entry to antenatal care refers to a first visit within the 12th week of gestation. Delayed access to antenatal care has not been extensively studied in Malaysia, whereas several studies have reported a high prevalence of late antenatal booking in developing countries. The objective of this study was to determine the factors and barriers associated with late antenatal booking and the level of knowledge about the timing of antenatal booking among women of childbearing age in the Lundu District of Sarawak. Methods This was a cross-sectional study among 284 pregnant women in all five Maternal and Child Health (MCH) Clinics of Lundu. Results The prevalence of late antenatal booking in Lundu was 28.2%. Unmarried women were more likely to book their pregnancy late compared to married women. The prevalence of late antenatal booking was also higher among unemployed women than those who were employed. Respondents without their own income also tended to book their pregnancy later than those who had their own income. Significantly, a high percentage of late antenatal booking was also reported among those who never utilize any contraceptive method, did not plan their pregnancy, those without a history of past medical illness or complications in a previous pregnancy and among those who have a problem with their marriage certificate. Those who booked their pregnancy beyond the 12th week of gestation were also reported to have a lower level of knowledge about the need for an antenatal booking, as compared to those who started their antenatal care early. Conclusions Unplanned pregnancy, marriage certificate issues, an absence of past medical illness and past obstetric complications were significant predictors of late antenatal booking. Correct and appropriate information relating to antenatal care should be delivered to the public. Health education and advocacy are vital to promote the importance of early antenatal booking to achieve the goal of safe motherhood.